Peran Kepala Sekolah Dalam Implementasi Pendidikan Karakter Melalui Gerakan Literasi Sekolah Dasar Yogyakarta - Nugroho, Irfan Adi; Nofrida, Eka Ridha; Megawati, Ida; Mardiana, Riska (Journal of Contemporary Issues in Primary Education, 2024)
This is a qualitative descriptive study. The research was conducted in an Elementary School in Yogyakarta. The sources of information in this study consisted of the school principal. Data collection techniques used observation, interviews, and documentation. Data validity was tested by increasing persistence and triangulation (source, technique, and time). Data analysis technique used Miles and Huberman model which consists of data collection, data reduction, data display, and conclusion drawing/ verification